Tuberculosis epididymitis presenting as an acute scrotum in a 65 year-old man undergoing BCG treatment for bladder cancer - M. Barns; E. Powell; M. Kuan (Urology Case Reports)
Intravesical immunotherapy with Bacillus Calmette-Guérin (BCG) is the cornerstone of treatment for non-muscle invasive bladder cancer (NMIBC). Intravesical BCG therapy is not without risks however, with complications ranging from bothersome to life-threatening occurring in approximately 1 % of cases. Tuberculous epididymitis is a rare but notable complication of BCG therapy, characterised by granulomatous inflammation of the epididymis. Here we present a rare case of tuberculosis epididymitis in a 65-year-old gentleman receiving intravesical BCG for treatment of his NMIBC. The authors wish to highlight the diagnostic consideration of tuberculosis epididymitis in patients presenting with scrotal pain while undergoing BCG treatment.